Do Non-work Practices in MNCs Operating in India Impact Organizational Commitment? - Awasthy, Richa; Gupta, Rajen K. (Organizations and Markets in Emerging Economies, 2011)
The present paper establishes the concept of Non-work Practices and explores its impact on organizational commitment. Drawing upon research conducted in four multinational corporations operating in India, the paper examines the degree to which non-work practices are accepted by Indian employees and their relationship with organizational commitment.  Concurrent mixed methodology was adopted in which both qualitative and quantitative data were collected. Template analysis was carried out to interpret employees’ feelings and experiences, and to identify the emerging trends. Factor analysis was carried out to find factors of non-work practices, and regression analysis was carried out to study relationship between organizational commitment and non-work practices. The article discusses the findings related to non-work practices: how these practices are experienced and perceived by Indian employees and what is their impact on the commitment of employees, which would in turn affect the effectiveness of the organization.It was found that since most of the non-work practices were transplanted from the parent company, they were perceived as alien (except in the Anglo-American MNC).  Host country employees showed little enthusiasm in carrying out those practices and hence these had no positive impact on their organizational commitment.
Keywords: India; multinational companies; non-work practices; organizational commitment